Coagulase-positive Staphylococci in Minas Frescal cheeses produced in family agroindustries - Mariana Barboza Vinha; Cláudia Lúcia de Oliveira Pinto; José Benício Paes Chaves (Revista do Instituto de Latícinios Cândido Tostes, 2018)
The aim of this work was to quantify Coagulase Positive Staphylococci (CPS) in Minas Frescal cheese produced in six non-inspected agroindustries, three of which use raw milk and three use pasteurized milk. Seventy-eight samples were collected, 46 of which (24 in agroindustry and 22 in commerce) were produced with pasteurized milk and 32 (15 in agroindustry and 17 in commerce) were made from raw milk. Cheeses produced with pasteurized milk had lower CPS counts (1.0 x 101 to 2.0 x103 UFC/g) and lower nonconforming samples (6.5%), which may be justified by post-pasteurization contamination due to failures at hygienic-sanitary conditions during the manufacture and marketing of the product. Cheeses made from raw milk presented higher contamination (6.0 x 102 to 3.6 x 106 CFU/g) and a higher percentage of nonconforming samples (75%), which can be attributed to contamination of the raw material. Informal cheeses are potentially capable of causing gastroenteritis and offer risk to public health. Family agroindustries must comply with sanitary requirements in order to offer safe products to consumers, avoid outbreaks, regularize production and expand marketing, providing the development and consolidation of this important activity in rural areas.